1981
DOI: 10.1093/geronj/36.6.642
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Aging and Endurance Exercise Upon the Mitochondrial Function of Skeletal Muscle

Abstract: Mitochondrial function was determined in sedentary-control animals, 150, 300 and 720 days of age, and in endurance-trained animals 300 and 720 days of age. The mitochondria were isolated from two regions of the cell of the gastrocnemius-plantaris muscle, subsarcolemmal and intermyofibrillar. State 3 respiration did not change with increasing age in control animals, but endurance training enhanced state 3 respiration in both the 300 and 720 day old trained animals. Age decreased the amount of intermyofibrillar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Endurance training has been shown to increase the activity of several mitochon drial enzymes in old rats [2,5,33]. The find ings of the present study that both CS and MDH activities increased with training in the 27-month-old rats were consistent with the consensus that the benefits of exercise training on skeletal muscle oxidative capac ity are not limited by old age.…”
Section: Discussionsupporting
confidence: 91%
“…Endurance training has been shown to increase the activity of several mitochon drial enzymes in old rats [2,5,33]. The find ings of the present study that both CS and MDH activities increased with training in the 27-month-old rats were consistent with the consensus that the benefits of exercise training on skeletal muscle oxidative capac ity are not limited by old age.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas both state 4 and state 3 respiration were significantly elevated in the IMF subfraction from young animals, mitochondria from muscle of old animals did not adapt to chronic contractile activity. Farrar et al [51] have previously shown that state 3 mitochondrial respiration was increased in SS and IMF subfractions isolated from young and old animals after a period of chronic muscle use. Notably, the training-induced increase in mitochondrial respiration was similar, or greater in the organelles isolated from the aged muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Chiu and Richardson (31) have suggested that reports of discrepancies are the consequence of comparing mitochondria isolated from different organisms or different tissues from the same organism, or organisms of different age, or use of different substrates employed in the bioenergetic measurements. A survey of the literature suggests that with increasing age there is a decrease in the number of mitochondria per cell (32,33). Also age-related decreases in the activity of many mitochondrial enzymes (33)(34)(35), most notably those involved in translocation, have been reported (23,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%